Analisis Efektivitas Platform Digital Pariwisata dalam Meningkatkan Keterlibatan UMKM Lokal di Era Pemerintahan Digital di Kota Tangerang - Ilham Ramdana; Megi Primagara; Toddy Aditya; Sukma Aditya Ramadhan (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political UMA), 2026)
This study analyzes the effectiveness of digital platforms in increasing the involvement of local MSMEs in the tourism sector in Tangerang City in the era of digital government. Digital transformation plays a crucial role in accelerating the adoption of technology, and the tourism sector is one of the most benefited. However, the involvement of MSMEs in digital platforms is still limited and unevenly distributed. This study adopts Technology Readiness Theory (TRT), Theory of Planned Behavior (TPB), and Digital Engagement Theory (DET) to identify factors that affect the involvement of MSMEs in digital platforms. The research method used is a quantitative approach with Structural Equation Modeling (SEM) techniques using SmartPLS software. The results show that both theories, TRT and TPB, have a positive effect on Digital Engagement, but TRT has a greater influence than TPB. The dimensions of optimism and innovativeness in TRT significantly encourage the adoption of digital technology (p < 0.05), while attitude, subjective norms, and perceived behavioral control in TPB influence the intentions and behaviors of technology adoption. In contrast, discomfort and insecurity show no significant effect. Unlike previous research that focused on general MSMEs, this study highlights tourism-oriented MSMEs operating in urban environments. This research provides important recommendations for policies that support the digitalization of MSMEs in the tourism sector, with a focus on digital literacy training, increasing trust in digital platforms, and simplifying the technology adoption process.